Understanding the pledge fulfilment of opposition parties using evidence from Portugal - Serra-Silva, S. (2022)
Under what conditions are opposition parties better at delivering on their electoral promises? Existing approaches to party mandates typically focus on governmental mandates and have disregarded the roles of other parties in parliament. However, such approaches encompass an imbalance regarding the comparison of pledge fulfilment between governing and opposition parties, and specially neglect the differences between permanent and alternating opposition. This article has the ambition to extend the mandate theory to opposition parties, exploring the conditions underlying their pledge fulfilment. Using a dataset of Portuguese opposition parties with more than 3000 electoral pledges for six different legislatures (1995-2015), our evidence suggests that: (1) alternating opposition parties have a significantly higher probability of fulfilling their mandate than permanent opposition; (2) opposition parties fulfill as much of their promises as the fulfillment costs decrease; (3) and the odds of opposition parties' mandate fulfillment is also increased when there is policy congruence between the pledge and a legislative initiative.